Calcium and metals are not evenly distributed in avian eggshells over their longitudinal section. (6th May 2019) - Orłowski, Grzegorz; Siekiera, Joachim; Karg, Jerzy; Tobolka, Marcin; Wuczyński, Andrzej; Kaługa, Ireneusz; Siekiera, Artur; Cyga-Döhner, Roman; Dudzik, Eliza
ABSTRACT: Whether Ca and other micronutrients are equally distributed in an avian eggshell over its longitudinal section and what portion of these local resources are utilized by developing embryos are unanswered questions in avian reproductive physiology. Here, we measured the thickness and concentrations of Ca and 16 other chemical elements (Al, As, Cd, Co, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Ni, Pb, Se, and Sr) in 4 shell regions (sharp pole, equator, shoulder, blunt pole) of White Stork ( Ciconia ciconia ) eggs representing different stages of embryonic development, from unresorbed eggshells to almost fully resorbed ones (with near-to-hatch embryos). We found that unresorbed eggshells displayed several significant differences in the concentrations of 15 elements (Al, As, Ca, Cd, Co, Cr, Fe, K, Hg, Mg, Mn, Na, Ni, Se, and Sr) between various regions of the same shell. Only 2 metals (As and Ca) showed a cross-sectional decrease in concentrations from the sharp pole to the blunt one. In particular, we observed that unresorbed eggshells at the blunt pole were less calcified (with 2.4% less Ca) compared to the sharp pole. In contrast, the concentrations of 6 other metals (Co, Fe, Mg, Mn, Na, and Se) peaked in the relatively less calcified region of the blunt pole, where concentrations (such as Se) were up to 10 times as high as in other regions of unresorbed eggshells. Our findings highlight that eggshells over their longitudinal sections are not chemically homogeneous. Surprisingly, however, and contrary to our expectations, we found that unresorbed eggshells were thinner (2.1–5.9% less depending on the region) and at the same time more strongly calcified than resorbed eggshells. This suggests that some modification has occurred in the shell structure and raises the question of thin-shelled eggs in populations of wild birds. RESUMEN: Si el Ca y otros micronutrientes están distribuidos uniformemente en la cáscara de huevo de las aves a lo largo de su sección longitudinal y qué porción de estos recursos locales son utilizados por los embriones en desarrollo son preguntas sin respuesta en la fisiología reproductiva de las aves que aún deben ser abordadas. Aquí, medimos el espesor y las concentraciones de Ca y otros 16 elementos químicos (Al, As, Cd, Co, Cr, Cu, Fe, Hg, K, Mg, Mn, Na, Ni, Pb, Se y Sr) en cuatro regiones de la cáscara (polo puntiagudo, ecuador, hombro, polo romo) de los huevos de Ciconia ciconia correspondientes a diferentes etapas de desarrollo embrionario, desde cáscaras de huevo no reabsorbidas hasta otras casi completamente reabsorbidas (con embriones prontos a eclosionar). Encontramos que las cáscaras de huevo no reabsorbidas muestran varias diferencias significativas en las concentraciones de 15 elementos (Al, As, Ca, Cd, Co, Cr, Fe, K, Hg, Mg, Mn, Na, Ni, Se y Sr) entre varias regiones de la misma cáscara. Solo dos metales (As y Ca) mostraron una disminución a lo largo de la sección transversal en las concentraciones desde el polo puntiagudo al polo romo. En particular, observamos que las cáscaras de huevo no reabsorbidas estuvieron menos calcificadas en el polo romo (con 2.4% menos Ca) en comparación con el polo puntiagudo. En contraste, las concentraciones de otros seis metales (Co, Fe, Mg, Mn, Na y Se) presentaron un valor máximo en la región relativamente menos calcificada del polo romo, donde las concentraciones (como de Se) fueron hasta diez veces más altas que en otras regiones de las cáscaras de huevo no reabsorbidas. Nuestros resultados subrayan que las cáscaras de huevo en sus secciones longitudinales no son químicamente homogéneas. Sorprendentemente, sin embargo, y en contraposición a nuestras expectativas, encontramos que las cáscaras de huevo no reabsorbidas fueron más delgadas (2.1–5.9% menos dependiendo de la región) y al mismo tiempo más fuertemente calcificadas que las cáscaras de huevo reabsorbidas. Esto sugiere que ha ocurrido alguna modificación en la estructura del huevo y plantea la pregunta sobre huevos de cáscara delgada en las poblaciones de aves silvestres.